MENINGKATKAN KINERJA ADMINISTRASI KEARSIPAN MELALUI PENGUATAN FUNGSI PENGAWASAN DI PERGURUAN TINGGI - Iskandar “Is”; Risman Risman (Sekolah Tinggi Ilmu Ekonomi Riau, 2026)
Abstract : This research was conducted at the Faculty of Sharia and Law, Sultan Syarif Kasim State Islamic University, Riau, located at Jalan H.R. Soebrantas No. 155 KM. 15, Simpang Baru Panam, Pekanbaru, Riau. The purpose and benefits of this research are to determine the influence of supervision on employee performance in the Archives Department of the Faculty of Sharia and Law, Sultan Syarif Kasim State Islamic University, Riau, in the future. The data collection techniques used in this study were questionnaires and interviews. The population in this study was all employees of the Faculty of Sharia and Law, Sultan Syarif Kasim State Islamic University, Riau, Pekanbaru, which in 2014 totaled 35 employees. For this study, the entire population was sampled, so the sampling method was carried out using a census method. Data analysis used simple linear regression analysis with the help of SPSS version 17 software. In addition, a partial test (t-test) was also conducted. The results of the study on the Effect of Supervision on Employee Performance in the Archives Department of the Faculty of Sharia and Law, Sultan Syarif Kasim State Islamic University, Riau, show that the calculated t-value is greater than the t-table, at 6.693 > 2.034. This indicates that Occupational Safety and Health has a significant influence on improving employee performance in the Archives Department of the Faculty of Sharia and Law, Sultan Syarif Kasim State Islamic University, Riau. The magnitude of the dependent variable's influence can be seen from the coefficient of determination (R-square) value, which is 0.576 or 57.6%. The remaining 42.4% is influenced by other independent variables not examined in this study.